Upgrade to Nucleus® 6 in Previous Generation Cochlear™ Sound Processor Recipients. - Biever, Allison; Gilden, Jan; Zwolan, Teresa; Mears, Megan; Beiter, Anne (Journal of the American Academy of Audiology, 2018)
Background: The Nucleus ® 6 sound processor is now compatible with the Nucleus ® 22 (CI22M)--Cochlear's first generation cochlear implant. The Nucleus 6 offers three new signal processing algorithms that purportedly facilitate improved hearing in background noise. Purpose: These studies were designed to evaluate listening performance and user satisfaction with the Nucleus 6 sound processor. Research Design: The research design was a prospective, single-participant, repeated measures design Study Sample: A group of 80 participants implanted with various Nucleus internal implant devices (CI22M, CI24M, Freedom ® CI24RE, CI422, and CI512) were recruited from a total of six North American sites. Data Collection and Analysis: Participants had their external sound processor upgraded to the Nucleus 6 sound processor. Final speech perception testing in noise and subjective questionnaires were completed after four or 12 weeks of take-home use with the Nucleus 6. Results: Speech perception testing in noise showed significant improvement and participants reported increased satisfaction with the Nucleus 6. Conclusion: These studies demonstrated the benefit of the new algorithms in the Nucleus 6 over previous generations of sound processors.